2022
DOI: 10.1055/s-0042-1756197
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Left Ventricular Thrombus Formation in Patients with Dilated Cardiomyopathy

Abstract: Background  Left ventricular thrombus (LVT) is a common complication of dilated cardiomyopathy (DCM), causing morbidity and mortality. Methods  This study retrospectively analyzed patients with DCM from January 2002 to August 2020 in Beijing Anzhen Hospital. Clinical characteristics were compared between the LVT group and the age and sex 1:4 matched with the LVT absent group. The receiver operator characteristic (ROC) curve was plotted to evaluate the diagnostic value of D-dimer pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…31 Sharma et al reported that an increase in LV internal diastolic dimension (LVIDD) was an independent predictors of LVT formation (OR, 1.10; 95% CI, 1.03-1.18; P = 0.004), and no patients with LVIDD < 60 mm had LVT formation. 19,32 Furthermore, we observed that patients with LVRR had a lower incidence of IHD at baseline. Previous research has shown that independent correlates of LVT resolution include non-ischaemic heart disease (HR, 2.74; 95% CI, 1.43-5.26; P = 0.002) and a smaller baseline thrombus area (HR, 0.66; 95% CI 0.45-0.96; P = 0.031).…”
Section: Discussionmentioning
confidence: 70%
“…31 Sharma et al reported that an increase in LV internal diastolic dimension (LVIDD) was an independent predictors of LVT formation (OR, 1.10; 95% CI, 1.03-1.18; P = 0.004), and no patients with LVIDD < 60 mm had LVT formation. 19,32 Furthermore, we observed that patients with LVRR had a lower incidence of IHD at baseline. Previous research has shown that independent correlates of LVT resolution include non-ischaemic heart disease (HR, 2.74; 95% CI, 1.43-5.26; P = 0.002) and a smaller baseline thrombus area (HR, 0.66; 95% CI 0.45-0.96; P = 0.031).…”
Section: Discussionmentioning
confidence: 70%
“…As one of the most prevalent cardiomyopathies worldwide with structural and functional abnormalities, DCM often leads to higher mortality [18][19][20] and there is no effective treatment to prevent the progression of DCM. Ferroptosis is a novel type of regulated cell death triggered by iron-dependent lipid peroxidation, which is involved in a variety of cardiovascular diseases.…”
Section: Discussionmentioning
confidence: 99%
“…14 However, there is no effective treatment for heterogeneous DCM patients, and the majority of DCM patients have poor outcomes and prognosis. [18][19][20] Moreover, the mechanism of heterogeneity in DCM patients remains uncertain. Therefore, there is an urgent need to explore the mechanism of heterogeneity in DCM patients and to identify potential targets.…”
Section: Discussionmentioning
confidence: 99%
“…Wu and colleagues reviewed retrospectively 3,134 patients with dilated cardiomyopathy and found that among 15 different variables, elevated D-dimer and reduced ejection fraction appeared to be independent risk factors for thrombus formation. 2 It is by now well known that patients with arterial thromboembolic disorders have an increased risk of venous thromboembolism (VTE)-and vice versa. Hu and colleagues have here investigated which cardiovascular risk factors are associated with increased or decreased risk of VTE in general, deep vein thrombosis (DVT), and pulmonary embolism.…”
mentioning
confidence: 99%
“…Wu and colleagues reviewed retrospectively 3,134 patients with dilated cardiomyopathy and found that among 15 different variables, elevated D-dimer and reduced ejection fraction appeared to be independent risk factors for thrombus formation. 2…”
mentioning
confidence: 99%